Endoscopic management of intentional foreign body ingestion: experience from a UK centre. Issue 2 (8th April 2021) - Yadollahi, Sina; Buchannan, Ryan; Tehami, Nadeem; Stacey, Bernard; Rahman, Imbadhur; Boger, Philip; Wright, Mark
Abstract : Objective: We report on the increasing incidence and outcomes from intentional foreign body ingestion (iFoBI) presenting to our hospital over a 5-year period. The aim was to assess the impact on services and to identify ways to safely mitigate against this clinical challenge. Design/method: We performed a retrospective observational study of all patients presenting to a university hospital between January 2015 and April 2020 with iFoBI with a focus on objects swallowed, timing of endoscopy and clinical outcomes. Results: 239 episodes of iFoBI in 51 individuals were recorded with a significant increase in incidence throughout the study period (Welch (5, 17.3)=15.1, p<0.001), imposing a high burden on staff and resources. Items lodged in the oesophagus were more likely to lead to mucosal injury (p=0.009) compared with elsewhere. Ingested item type and timing of endoscopy were not related to complications (p=0.78) or length of stay (p=0.8). In 12% of cases, no objects were seen at endoscopy. Conclusion: In all except those patients with oesophageal impaction of the object on radiograph, there is no need to perform endoscopic extraction out of hours. A subset of cases can avoid endoscopy with an X-ray immediately prior to the procedure as a significant proportion have passed already. We discuss more holistic approaches to deal with recurrent attendances.